Cover Feature: Tuning the Color Temperature of White‐Light‐Emitting Electrochemical Cells by Laser‐Scanning Perovskite‐Nanocrystal Color Conversion Layers (ChemPlusChem 4/2018). Issue 4 (13th March 2018) - Wu, Wen‐Kuang; Wang, Cheng‐Ming; Chan, Ming‐Che; Lien, Jiun‐Yi; Su, Yong‐Ming; Sarma, Monima; Yang, Zu‐Po; Su, Hai‐Ching; Wong, Ken‐Tsung; Wang, Sue‐Lein
Abstract : The cover feature shows a white‐light‐emitting electrochemical cell (WLEC) composed of the non‐doped blue‐green LEC and the single composition perovskite nanocrystals, which serves as a color conversion layer. A laser scanning technique widely tunes the color temperature of the WLEC by modifying the perovskite nanocrystals. This approach has potential to simplify fabrication of the light sources for bedrooms, living room and working place. Details are given in the Full Paper by H. C. Su, Z. P. Yang and co‐workers onpage 239 in Issue 4, 2018 (DOI:10.1002/cplu.201700422 ).